2021
DOI: 10.1111/lam.13593
|View full text |Cite
|
Sign up to set email alerts
|

Compost as an untapped niche for thermotolerant yeasts capable of high‐temperature ethanol production

Abstract: Efficient bioethanol production from lignocellulosic biomass requires thermotolerant yeasts capable of utilizing multiple sugars, tolerating inhibitors and fermenting at high temperatures. In this study, 98 thermotolerant yeasts were isolated from nine compost samples. We selected 37 yeasts that belonged to 11 species; 31 grew at 45°C; 6 strains grew at 47°C, while 9 yeasts could utilize multiple sugars. Many yeast isolates showed high ethanol production in the range of 12–24 g l−1, with fermentation efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…And though K. marxianus can be isolated from rotting fruit 40,41 , it may not have specialized narrowly to such substrates: a neighboring clade that includes Saccharomyces cerevisiae produces more ethanol than do any of the Kluyveromyces species 6 , suggesting a weaker drive in the latter toward this putative mechanism to kill off microbial competitors in high-sugar environments. Perhaps most compelling among microbial ecology findings is the prevalence of K. marxianus in decomposing plant material beside fruit, including leaf litter and pine needles 42 , cow dung 19 and industrially processed cocoa beans 43 , agave 44 , and sugar cane 16,45 . If the ancestral niche for K. marxianus included plant substrates of this kind, the yeast could have specialized in rapid metabolism of free sugars, leaving the breakdown of lignocellulosic plant cell wall components to other fungal saprotrophs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And though K. marxianus can be isolated from rotting fruit 40,41 , it may not have specialized narrowly to such substrates: a neighboring clade that includes Saccharomyces cerevisiae produces more ethanol than do any of the Kluyveromyces species 6 , suggesting a weaker drive in the latter toward this putative mechanism to kill off microbial competitors in high-sugar environments. Perhaps most compelling among microbial ecology findings is the prevalence of K. marxianus in decomposing plant material beside fruit, including leaf litter and pine needles 42 , cow dung 19 and industrially processed cocoa beans 43 , agave 44 , and sugar cane 16,45 . If the ancestral niche for K. marxianus included plant substrates of this kind, the yeast could have specialized in rapid metabolism of free sugars, leaving the breakdown of lignocellulosic plant cell wall components to other fungal saprotrophs.…”
Section: Discussionmentioning
confidence: 99%
“…The ecological driving forces for unique traits in K. marxianus are unknown, though sampling studies have found this species at high prevalence in high-temperature agricultural and domestic compost [18][19][20] . We reasoned that some phenotypes unique to K. marxianus could have evolved as a product of adaptation to high-temperature or other niches, and that at relevant loci, we could detect evidence for positive selection from sequence data.…”
Section: Widespread Evidence For Positive Selection Along the K Marxi...mentioning
confidence: 99%